Estrés académico y motivación del aprendizaje en educación virtual de estudiantes de Medicina de la Universidad Nacional de Loja - Cevallos Esparza, Marjorie Salomé (2023)
The pandemic produced by the SarsCov2 virus triggered students and teachers to modify their usual routine due to confinement, therefore the universities demanded adaptation to a virtual modality in an unexpected way and caused stressful stimuli in students and teachers. Teleeducation was the biggest challenge for the students because they did not have a space in their home that was adequate to receive the classes, as well as problems with the Internet connection, difficulties in maintaining concentration, learning how to use digital platforms, symptoms of stress or anxiety due to the lack of adequate communication when receiving classes or having to carry out tasks with ambiguous explanations by teachers, which is why the purpose of this research was to determine the level of stress and categorize the motivation of learning of the Medicine students of the National University of Loja, with a prospective cross-sectional quantitative approach, a sample of 132 students who met the inclusion and exclusion criteria, to whom the Cognitive Systemic Inventory (SISCO) and the Motivation Scale of the Learning and attributional styles. CEAP scale48. SEMAP-01 subscale evidencing a high level of stress in 80.3%, unlike the average level of stress with 19%, in terms of learning motivation, deep motivation represented 55.3%, and motivation with a lower percentage. superficial 36.36%, a statistically significant relationship was determined between both variables (p< 0.0001) which were predominant in the female sex